Emotional Engineering, Vol.7 The Age of Communication - Fukuda, Shuichi (Springer International Publishing : Imprint: Springer, 2019)
This book demonstrates that emotion is a highly influential component in creating a new society and new engineering, revealing the importance of emotion in various aspects of the Connected World. It addresses a wide variety of topics, but with this one underlying aim throughout. Further, it stands out for the approach it takes to the Internet of Things and the Connected Society. The contributing authors illustrate that humans are essentially either playmakers or playing managers, with teamwork and play being crucial aspects of our lives. They argue that strategy is becoming increasingly important, and consider the most adaptable strategy, one that will allow us to respond to today's quickly and radically changing situations. The book is particularly focused on the Connected Society as the point of departure, and explores what motivates humans, what decisions they should make, and what actions they should take. With engineering quickly moving from product development to experience development, and the role of emotion in engineering becoming increasingly apparent, this book offers a timely and valuable resource for engineers and researchers alike. .